Autocrine C‐peptide protects INS1 β cells against palmitic acid‐induced oxidative stress in peroxisomes by inducing catalase. Issue 3 (30th May 2020) - Luppi, Patrizia; Drain, Nicholas; To, Ramsey; Stolz, Donna; Wallace, Callen; Watkins, Simon; Drain, Peter
Abstract: Aims: C‐peptide, produced by pancreatic β cells and co‐secreted in the bloodstream with insulin, has antioxidant properties in glucose‐ and hydrogen peroxide (H2 O2 )‐exposed INS1 β cells. Palmitic acid, the most physiologically abundant long‐chain free fatty acid in humans, is metabolized in peroxisomes of β cells accumulating H2 O2 that can lead to oxidative stress. Here, we tested the hypothesis that C‐peptide protects β cells from palmitic acid‐induced stress by lowering peroxisomal H2 O2 . Materials and methods: We exposed INS1 β cells to palmitic acid and C‐peptide in the setting of increasing glucose concentration and tested for changes in parameters of stress and death. To study the ability of C‐peptide to lower peroxisomal H2 O2, we engineered an INS1 β cell line stably expressing the peroxisomal‐targeted H2 O2 sensor HyPer, whose fluorescence increases with cellular H2 O2 . An INS1 β cell line stably expressing a live‐cell fluorescent catalase reporter was used to detect changes in catalase gene expression. Results: C‐peptide protects INS1 β cells from the combined effect of palmitic acid and glucose by reducing peroxisomal H2 O2 to baseline levels and increasing expression of catalase. Conclusions: In conditions of glucolipotoxicity, C‐peptide increases catalase expression and reduces peroxisomal oxidative stress and death of INS1 β cells. Maintenance of C‐peptide secretion is a pro‐survival requisite for β cells in adverse conditions. Loss of C‐peptide secretion would render β cells more vulnerable to stress and death leading to secretory dysfunction and diabetes. Abstract : Proinsulin C‐peptide has antioxidant properties in glucose‐ and hydrogen peroxide (H2 O2 )‐exposed INS1 beta cells. Here, we tested the hypothesis that C‐peptide protects beta cells from palmitic acid‐induced stress by lowering peroxisomal H2 O2 . We exposed INS1 β cells to palmitic acid and C‐peptide in the setting of increasing glucose concentration and tested for changes in parameters of stress and death. To study the ability of C‐peptide to lower peroxisomal H2 O2, we engineered an INS1 β cell line stably expressing the peroxisomal‐targeted H2 O2 sensor HyPer, whose fluorescence increases with cellular H2 O2 . An INS1 beta cell line stably expressing a live‐cell fluorescent catalase reporter was used to detect changes in catalase gene expression. We found that in conditions of glucolipotoxicity, C‐peptide increases catalase expression and reduces peroxisomal oxidative stress and death of INS1 beta cells. We conclude that maintenance of C‐peptide secretion is a pro‐survival requisite for beta cells. Therefore, loss of C‐peptide secretion would render beta cells more vulnerable to stress leading to secretory dysfunction and diabetes.